2011
DOI: 10.1007/s10008-011-1476-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chloride concentration and pH on pitting corrosion of AA7075 aluminum alloy coated with phenyltrimethoxysilane

Abstract: The effect of chloride ion concentration and pH of solution on the corrosion behavior of aluminum alloy AA7075 coated with phenyltrimethoxysilane (PTMS) immersed in aqueous solutions of NaCl is reported. Potentiodynamic polarization, linear polarization, open circuit potential, and weight loss measurements were performed. The surface of samples was examined using SEM and optical microscopy. Elemental characterization of the coating by secondary ion mass spectrometry indicates an intermediate layer between coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…During the in situ observation of pit growth, black flocculent precipitates were spewed out from holes on the metal covers at all applied potentials. More metal cations need more chloride anions to sustain the electroneutrality inside the pit [5,6]. Therefore, as the pit growth time and applied potential increased, the concentration of metal cations and chloride anions increased continuously during stable propagation.…”
Section: Chemical Compounds Of Internal Electrolyte Of Stable Pitsmentioning
confidence: 97%
See 2 more Smart Citations
“…During the in situ observation of pit growth, black flocculent precipitates were spewed out from holes on the metal covers at all applied potentials. More metal cations need more chloride anions to sustain the electroneutrality inside the pit [5,6]. Therefore, as the pit growth time and applied potential increased, the concentration of metal cations and chloride anions increased continuously during stable propagation.…”
Section: Chemical Compounds Of Internal Electrolyte Of Stable Pitsmentioning
confidence: 97%
“…For a certain applied potential, the current density of a stable pit is always higher than a metastable pit. This may indicate that high current density can maintain stable pit propagation [3][4][5][18][19][20][21]. For the occluded pits, the pitting current density of a single stable pit increases with applied potential.…”
Section: Pitting Current Densities Of Stable Pitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant matter consumes carbon dioxide and affects the pH during daylight hours [1,81]. The carbon dioxide content in seawater (close to the surface) is influenced by the exchange with carbon dioxide in the atmosphere [1].…”
Section: Phmentioning
confidence: 99%
“…Many researchers have studied the mechanism of steel corrosion in marine and offshore environments. Jyoti et al [5] summarized previous research work and reported that temperature [6], pH value [7], salinity [8], dissolved oxygen [9], and water velocity [10] were the main physical factors that affected the corrosion responses of steel. Besides the investigation of corrosion factors, other studies have focused on mechanism optimization.…”
Section: Introductionmentioning
confidence: 99%